PERENIALISM IN ERA GLOBALIZATION - Khudaeri, Alwi (Universitas Islam Negeri Antasari Banajarmasin, 2017)
Perenialisme is a stream in education who were born in the 20th century, as a reaction to progressivism education. Globalization has now entered the public worldwide, resulting interdependence in all aspects of life. Globalization has brought a broad impact in people's lives. The effect it has not all are positive there is also a negative for the life of air-society, nation and bernegera. For Indonesia, this era is a challenge. In order to prepare the next generation is not lost their identity sebagaai Indonesian nation. Substance Perenialisme philosophy is one alternative that should be applied in education.